Structural Wall Facade Reconstruction of Scanned Scene in Point Clouds - NING, X. (Stefan cel Mare University of Suceava, 2021)
Representation of wall facade in 3D scene is important for scene understanding and reconstruction. Doors and windows are essential elements of wall facade, which enrich the models of indoor buildings. In order to reconstruct the wall facade with detailed wall opening (doors and windows) information from point cloud, an improved automatic reconstruction approach is proposed in this paper. Specifically, we first detect the occlusion area on the wall by ray-tracing method. Then, the interested wall facade is segmented from scenes, and the contour and feature lines of the wall surface are extracted through the analysis of spatial occupancy. Third, the wall point cloud is transformed into a 2D cell complex. The wall surface is finally reconstructed through the wall opening identification based on graph cut. Experimental results demonstrate that our method has better performance in detail description, feature line extraction and opening area detection of the scene point cloud than existing state-of-the-art methods.